Selected works of Govind Ballabh Pant - Pant, Govind Ballabh; Nanda, B R (Ed) (New Delhi Oxford University Press, 2001)
The fifteenth volume covers the period from September 1951 to March 1953 and deals with the general elections held under the constitution and the formation of a new congress Ministry in Uttar Pradesh under the leadership of Govind Vallabh Pant who became
Keywords: Pant, Govind Ballabh-Biography; Pant,Govind Ballabh-Oratory; Public speaking